2018
DOI: 10.5539/hes.v8n4p104
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Higher Education for Students with Disabilities in China: What Do the University Teachers Think?

Abstract: Inclusive higher education is a path to protect the educational rights of university students with disabilities. University teachers’ attitudes toward students with disabilities, and towards their inclusion in universities, are a key factor that will affect the development of inclusive higher education. This study used a questionnaire to explore an overall perspective of how university teachers in China view inclusive higher education from emotional, cognitional and conative aspects. Their responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 18 publications
(20 reference statements)
0
26
0
6
Order By: Relevance
“…For example, some academics refuse to adapt their exams and materials, or they use teaching methods that do not promote inclusivity (Mutanga, 2018;Yssel et al, 2016). Moreover, various works have highlighted that the knowledge, attitudes, and good will of academics to offer curricular adaptations are critical factors for the success of students with disabilities Leyser et al, 2011;Zhang et al, 2019). Considering this situation, students demand more trained, informed, and aware academic staff (Vickerman & Blundell, 2010).…”
Section: Learning Barriers For Students With Disabilitiesmentioning
confidence: 99%
“…For example, some academics refuse to adapt their exams and materials, or they use teaching methods that do not promote inclusivity (Mutanga, 2018;Yssel et al, 2016). Moreover, various works have highlighted that the knowledge, attitudes, and good will of academics to offer curricular adaptations are critical factors for the success of students with disabilities Leyser et al, 2011;Zhang et al, 2019). Considering this situation, students demand more trained, informed, and aware academic staff (Vickerman & Blundell, 2010).…”
Section: Learning Barriers For Students With Disabilitiesmentioning
confidence: 99%
“…A research study from China further found that teachers generally displayed positive attitudes and awareness of the rights of students with disabilities. However, teachers lacked motivation, knowledge, skills and effective strategies for providing support to students with disabilities (Zhang, Rosen, Cheng and Li, 2018). In some instances, the "lenience of professors concerning course requirements" was also observed: "…I had certain situations with teachers when I said: "Look, you cannot pass the student if he/she does not have the competences, this is a big problem".…”
Section: Challenges/difficulties For Students With Disabilities In Thmentioning
confidence: 99%
“…Faculties can allocate a disability services office that concentrates in providing academic support and technical assistance in regard to SWDs (Tinklin et al, 2004). Universities in China have a dedicated a 'Service Center for SWDs' that assists them in their educational processes while also facilitating their connections with academic staff and peers (Zhang, Rosen, Cheng& Li, 2018). Other institutions might have a designated officer supervised under a senior manager tasked with the responsibility of assisting SWDs (Tinklin et al, 2004).…”
Section: H3mentioning
confidence: 99%
“…The motivation to learn and transfer skills to their respective educational environment can be observed more in academics who are more willing to accommodate SWDs (Murray et al, 2008). It can therefore be implied that WtA.SWDs, the need for professional development for SWDs and the effectiveness of training are inter-related (Park, Roberts& Stodden, 2012;Zhang et al, 2018). There has been little empirical evidence to support this and hence, the following is hypothesised.…”
Section: H5mentioning
confidence: 99%
See 1 more Smart Citation